Sedimentology and ichnology of Neogene Coastal Swamp deposits in the Niger Delta Basin, Nigeria - Ezeh, Sunny C.; Mode, Wilfred A.; Ozumba, Berti M.; Yelwa, Nura A. (Geologos, 2016)
Often analyses of depositional environments from sparse data result in poor interpretation, especially in multipartite depositional settings such as the Niger Delta. For instance, differentiating channel sandstones, heteroliths and mudstones within proximal environments from those of distal facies is difficult if interpretations rely solely on well log signatures. Therefore, in order to achieve an effective and efficient interpretation of the depositional conditions of a given unit, integrated tools must be applied such as matching core descriptions with wireline log signature. In the present paper cores of three wells from the Coastal Swamp depositional belt of the Niger Delta are examined in order to achieve full understanding of the depositional environments. The well sections comprise cross-bedded sandstones, heteroliths (coastal and lower shoreface) and mudstones that were laid down in wave, river and tidal processes. Interpretations were made from each data set comprising gamma ray logs, described sedimentological cores showing sedimentary features and ichnological characteristics; these were integrated to define the depositional settings. Some portions from one of the well sections reveal a blocky gamma ray well log signature instead of a coarsening-upward trend that characterises a shoreface setting while in other wells the signatures for heteroliths at some sections are bell blocky in shaped rather than serrated. Besides, heteroliths and mudstones within the proximal facies and those of distal facies were difficult to distinguish solely on well log signatures. However, interpretation based on sedimentology and ichnology of cores from these facies was used to correct these inconsistencies. It follows that depositional environment interpretation (especially in multifarious depositional environments such as the Niger Delta) should ideally be made together with other raw data for accuracy and those based solely on well log signatures should be treated with caution.